Modern view of mechanisms of chronic pain syndrome in patients with knee joint damage - Buhaiov, Oleksandr; Tarabrin, Oleg (Journal of Education, Health and Sport, 2024)
Chronic pain accompanies most diseases of the musculoskeletal system. A feature of this type of pain is its duration, for more than three months, and the absence of a damaging factor. The purpose of our review was to systematize data on the latest research on the pathogenesis of chronic pain syndrome in the knee joint and to consider modern theories of neuropathic pain. A generalization and analysis of scientific publications over the last 5 years on the topic of this study was carried out. To search for literature sources, databases and search engines were used: Web of Science, Scopus, WorldWideScience, CORE, PubMed, and Google Scholar by keywords of the research topic. After conducting a review of the literature, we found out that experts have long been interested in the issue of inconsistency of the X-ray picture in rheumatoid arthritis and pain sensations. Daily loads experienced by the knee joint increase with increasing axial movements. Traumatic and non-traumatic diseases of the knee joint are common pathologies, and the percentage of such patients increases with age. Today, joint diseases occupy the first place and can lead to loss of working capacity, disability. Recent studies have discovered the mechanisms of neuropathic pain, and in recent years the term "neuroplastic" pain has appeared. Its appearance is associated with changes in the processing of nociceptive pain and the formation of new nerve circuits that cause long-term irritation of nociceptors and inhibit the antinociceptive system, due to the blockade of the periaqueductal and rostroventromedial descending pathways, and on the periphery due to the blockade of GABA-ergic synapses.Chronic pain is a consequence of changes in the limbic system, as such pain is often accompanied by the development of depression. Manifestations of neuropathic pain are heterogeneous in terms of pathophysiological mechanisms, etiology and clinical picture. Symptoms of pain depend on the nature of the injury, as well as factors such as genetics and gender. According to research, chronic neuropathic pain is more common in women and people over 50 years of age with a predominant lesion of the lower back and lower limbs. The aging of the population, the spread of diseases associated with hypodynamia and obesity will increase the percentage of people with manifestations of neuropathic pain in the future. Conclusions. Understanding the pathogenetic mechanisms of neuropathic pain is important for the development of new therapeutic strategies targeting specific neural mechanisms.